KEKUASAAN DAN AGAMA Perspektif Budaya Timur - Antonius Abimantrono (Litbang STFT Widya Sasana Malang, 2004)
This study contains a reconstruction of the anthropological perspective that until now seems to be dominated by the West (Geertz). The basic idea is that the category of power and dominion is alien to the idea of harmony predominant in the East. With an epistemological note the author describes the birth and growth of the Javanese mentality through history and influences upon the attitude of the today Javanese people. To begin with the “Keraton” (court) mentality that is cosmological and mythological in character, the subordinates (the “Priyayi”) share and inherit the same view through mystical experiences and symbols. In line with this, basic attitude becomes like “private religion” of the “Priyayi”. Instead of being dependent they claim to be independent through identification with the Whole as the goal of harmonization. With the help of Weber’s analysis the article shows the parallel with the idea of the “world-view” that is current among the “conservatives” and at the same time shows the difference between the “Priyayi” mentality and the attitude of the Euroepean bourgeoisie because of the lack of historical phase of institutionalisation.